Cured malakoplakia of the renal allograft followed by long-term good function: a case report - Honsova, Eva; Lodererova, Alena; Slatinska, Janka; Boucek, Petr (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2012)
BACKGROUND: Malakoplakia is an unusual chronic inflammatory disease with distinctive histopathological features rarely involving the parenchyma of a transplanted kidney, and to date less than ten cases have been reported. METHODS AND RESULTS: We present a case of malakoplakia of a kidney graft in a 31 year old woman after simultaneous kidney and pancreas transplantation, which was successfully treated with quinolones. After the treatment of malakoplakia, she was monitored regularly, and her renal and pancreas grafts functioned well for the following 9 years, which is 12 years post transplantation. Moreover, 1 year after treatment of malakoplakia she became pregnant and gave birth to a healthy child. CONCLUSION: Evaluation of a kidney biopsy sample represents the key to diagnosis of malakoplakia which is important for correct patient management. Treatment with antibiotics with intracellular penetration (quinolone type) may result in curing the disease. According to our knowledge, this is the first case of allograft renal malakoplakia after combined kidney and pancreas transplantation.
Keywords: Kidney Diseases; malakoplakie; diabetes mellitus 1. typu; transplantace slinivky břišní; chinolony; antibakteriální látky; Adult; Pancreas Transplantation; dospělí; nemoci ledvin; Malacoplakia; Quinolones; lidé; ženské pohlaví; Anti-Bacterial Agents; Kidney Transplantation; Humans; transplantace ledvin; Diabetes Mellitus, Type 1; Female